Rancang Bangun Website Desa Sebagai Media Informasi Pengenalan Potensi Desa Tumbang Manjul - Sulistia, Ciola Dwi; Geges, Septian (Universitas Palangka Raya, 2022)
Tumbang Manjul Village is a remote village located in the forest in Seruyan Hulu District, Seruyan District, Central Kalimantan Province. Tumbang Manjul Village has a lot of potential that must be known by the community so that Tumbang Manjul Village can be recognized. With this potential, the village of Tumbang Manjul can also contribute to the community outside the village to take advantage of the results of the village. Based on the background provided, a Village Website Design was made as an Information Media for Introducing the Potential of Tumbang Manjul Village, Seruyan Hulu District, Seruyan Regency, Central Kalimantan Province so that it could facilitate the village of Tumbang Manjul to promote the village's potential. The methodology used in making this village website is the waterfall method with stages, namely Requirement Analysis described using a Flowchart, System Design described through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and database. Implementation with the programming languages ​​used, namely HTML, PHP, CSS, Bootstrap Javascript, and MySQL. The final stage is Testing using the Blackbox Method. On this website there are several features, namely the village government, facilities, village potential, and contacts that can be accessed by website visitors with the aim that visitors can view information about the village of Tumbang Manjul. This website is also managed by an admin who has the right to manage data on the Tumbang Manjul village website.